This Is Not ‘Interesting’ Research: Authentically Co-Creating Participatory Action Research in UK’s Post-Covid Culture Industries - Rai, Amit; Essilfie, Will (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This essay explores methodological, ethical, and practical aspects of authentically co-creating participatory action research (PAR) in post-Covid 19 participatory arts contexts in the UK. It analyses the limits and possibilities of PAR methods into leadership pathways in the UK’s arts and culture sector. In critical dialogue with decolonial and intersectional frameworks that seek to challenge and transform institutionalised privilege in the wake of the Covid pandemic, we investigate the financialisation of participatory strategies of cultural co-creation, with a particular focus on questions of racial and class dynamics in the arts. This essay develops a decolonial political ontology of PAR through a critique of both authenticity and its financialisation in participatory action research projects. Drawing on recent critical analyses of ‘post-extractivism’ and ‘co-creation’ in participatory research, we suggest that the recent financialisation of ‘impactful’ participation is an increasingly important but neglected ‘matter of concern’ for critical PAR methodologies.